The effect of fiscal and monetary policies, trade openness and balance of payment on the total output in Malaysia - Mahmood, Ali Shakir (School of Business Innovation and Technopreneurship, 2018)
Relevant with the formulation of research questions above, this study is designed to achieve the objectives; as follows; to analyze the influence of fiscal policy on the total output in Malaysia; to evaluate the effect of fiscal policy on total output during the 1997-98 period of financial crisis in Malaysia; to measure the influence of monetary policy on the total output in Malaysia; to examine the impact of monetary policy on total output during the 1997-98 period of financial crisis in Malaysia; to determine the effect of trade openness on the total output in Malaysia; to investigate the impact of balance of payment on the total output in Malaysia.